Desigualdades geométricas em ambientes subestáticos e pseudo-hiperbólicos. - Rodrigues, Diego de Sousa (2018)
This thesis is divided in two parts. In the first one, using the inverse mean curvature flow, we prove two weighted geometric inequalities that hold for strictly mean convex and star-shaped hypersurfaces in Euclidean space. The first one involves the weighted area and the area of the hypersurface and also the volume of the region enclosed by the hypersurface. The second one involves the total weighted mean curvature and the area of the hypersurface. Moreover, versions of the first inequality for the sphere and for the Ressner-Nordström-AdS manifold are proven. We end the first part with an example of a convex surface for which the ratio between the polar moment of inertia and the square of the area is less than that of the round sphere. In the second part, using spinorial techniques, we prove, for a class of pseudo-hyperbolic ambient manifolds, a Heintze-Karcher type inequality. We then use this inequality to show an Alexandrov type theorem in such spaces.